Atherosclerotic disease and diabetes mellitus - Martha Lilac Ketisha Antoine, Malyn; Xu, Yancheng; Kossi Djakpo, Dodji (International Journal of Medicine, 2020)
The macro-vascular complications (cardiovascular, neurovascular and peripheral vascular diseases) observed in diabetic patients usually develop secondary to the presence of atherosclerotic diseases. In diabetic patients chronically elevated blood glucose levels play a major role in contributing to the development of the disease; however, in addition to hyperglycaemia, other factors such as hypertension, dyslipidaemia and obesity also contribute to the development of this condition. Despite the fact that further research is required to fully establish the relationship between hyperglycaemia and the development of atherosclerotic plaques in diabetic patients, three major pathways have already been identified for the role they play in the pathogenesis of atherosclerosis. These pathways are identified as follows: 1. non-enzymatic glycosylation of lipids and proteins 2. oxidative stress 3.Protein kinase C. This review discusses how hyperglycaemia influences the development of atherosclerosis which further leads to the development of major vascular complications in diabetic patients.Â